2016
DOI: 10.12737/16848
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between the ULF wave power spatial distribution and auroral oval boundaries

Abstract: The location of the auroral oval boundaries has been mapped onto the Pc5 wave power spatial distribution. The poleward and equatorward boundaries of auroral oval are estimated using either the BAS database based on UV observations of the aurora by the IMAGE satellite or the OVATION model based on the DMSP particle data. The epicenter of the spectral power of broadband fluctuations in the Pc5 band during storm growth phase is mapped inside the auroral oval. During the storm recovery phase, the spectral power of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Furthermore, if the dawn-dusk asymmetry were predominantly due to asymmetries in ionospheric conductivity we would see the asymmetry for more parameters and latitudes than in our analysis above. However, the relationship between ionospheric conductivity and solar wind properties (e.g., Newell et al, 2009) and the related effect of the auroral oval on observed wave power (Kozyreva et al, 2016;Pilipenko et al, 2001;Simms et al, 2006) are likely to have additional effects that should be investigated in future, perhaps with a secondary set of hypotheses, or with an expanded set of parameters if they could be causally established.…”
Section: Hypotheses 2: Power Signature Of External Driversmentioning
confidence: 99%
“…Furthermore, if the dawn-dusk asymmetry were predominantly due to asymmetries in ionospheric conductivity we would see the asymmetry for more parameters and latitudes than in our analysis above. However, the relationship between ionospheric conductivity and solar wind properties (e.g., Newell et al, 2009) and the related effect of the auroral oval on observed wave power (Kozyreva et al, 2016;Pilipenko et al, 2001;Simms et al, 2006) are likely to have additional effects that should be investigated in future, perhaps with a secondary set of hypotheses, or with an expanded set of parameters if they could be causally established.…”
Section: Hypotheses 2: Power Signature Of External Driversmentioning
confidence: 99%
“…d. Maps of magnetic perturbations and the synoptic open/?closed boundary of the magnetosphere in both polar caps (Urban et al, 2011). e. Statistical maps of magnetic perturbations (Pothier et al, 2015;Weimer et al, 2010) (Kozyreva et al, 2016) and other ULF wave categories superposed on magnetospheric regions such as the polar cap, auroral zone, plasmatrough, and plasmasphere. g. Global and regional maps and parameterizations of geomagnetic disturbances (and time derivatives) that drive ground-induced currents (e.g., Carter et al, 2016;Love et al, 2016;Woodroffe et al, 2016).…”
Section: Higher-level Data Productsmentioning
confidence: 99%
“…A demarcation of the cusp soft electron precipitation can be determined by comparing the equatorward boundary of the red (630.0 nm) auroral emission along the photometer meridian scanning [Lorentzen et al, 1996]. Precipitation of soft electrons with 0.1-1 keV energies is a good indicator of open magnetic field lines and corresponds to the cusp aurora dominated by the red emission (Rayleigh intensity ratio 630.0/557.7>1) [Lorentzen, Moen, 2000;Johnsen, Lorentzen, 2012]. However, dayside auroral optical measurements can be made during winter months only.…”
Section: Ionospheric Footprint Of the Dayside Ocb From Optical And Hfmentioning
confidence: 99%
“…Geomagnetic pulsations in the Pc5-6 band (periods about 3-15 min) have been known to be a persistent feature of the ULF activity at dayside high latitudes [Engebretson et al, 1995;Francia et al, 2005]. Morphologically, these high-latitude long-period pulsations (sometimes called Irregular Pulsations at Cusp Latitudes [Bolshakova et al, 1988]) differ from well-known quasi-monochromatic Pc5 waves observed at auroral latitudes [Kozyreva et al, 2016]. The specific high-latitude near-noon pulsations could be a signature of the magnetopause surface eigenmodes [Plaschke et al, 2009a;Hartinger et al, 2015] or oscillations of the last field lines [Lanzerotti et al, 1999;Urban et al, 2011].…”
Section: High-latitude Ulf Wave Activity As a Possible Ocb Discriminatormentioning
confidence: 99%